Immune Checkpoint Molecules in Reproductive Immunology - Miko, Eva; Meggyes, Matyas; Doba, Katalin; Barakonyi, Aliz; Szereday, Laszlo (Frontiers in Immunology, 2019)
Immune checkpoint molecules, like CTLA-4, TIM-3, PD-1, are negative regulators of immune responses to avoid immune injury. Checkpoint signaling in immune cells is involved in the immune defense of infections, prevention of autoimmunity, transplantation and tumor immune evasion. Maternal-fetal immunotolerance represents a real immunological challenge for the immune system of the mother: beside acceptance of the semiallogeneic fetus, the maternal immune system has to be prepared for immune defense mostly against infections. In this particular situation, the role of immune checkpoint molecules could be of special interest. In this review, we describe current knowledge on the role of immune checkpoint molecules in reproductive immunology.